Total Ischemic Time Versus Door-To-Balloon Time As An Outcome Predictor In St-Elevation Myocardial Infarction - Sigal, MD, Adam; Rajagopalan, MD, Priya; Fadahunsi, MD, Opeyemi; Koslow, MD, Michael; Wasser, PhD, Tom; Mengel, RN, Vanessa Cambria; Barbera, MD, Charles (Journal of Medical Biomedical and Applied Sciences, 2018)
BACKGROUND Acute Coronary Syndrome is a common presenting condition to the emergency department and early reperfusion therapy for patients with an ST-Elevation Myocardial Infarction (STEMI) with Percutaneous Coronary Intervention is the recommended treatment. The American Heart Association / American College of Cardiology has a 60 minutes goal for restoration of coronary flow from the time of patient arrival. OBJECTIVE To review the impact of rapidly identifying STEMI patients and expediting transfer to the interventional cardiology suite on restoration of blood flow times and metrics of cardiac injury, such as peak troponin and ejection fraction. To review the impact of total ischemic time on similar metrics. METHODS We conducted a single site retrospective review on STEMI patients undergoing the expedited process for reperfusion compared to standard process. RESULTS Expedited transfer of patients to the cardiac catheterization suite resulted in significantly lower door-to-balloon times for patients undergoing the â€œdrive-byâ€ process (mean 31.03, SD 4.05 vs mean 68.72, SD 45.09, p < 0.001), compared to usual care. The improved times, however, did not translate into improved metrics of peak troponin value or LVEF. There was a significantly lower peak troponin level (mean 57.14, SD 86.51 vs 97.73, SD 152.43, p=0.017) and a greater LVEF percent at six months (56.41, SD 10.46 vs 52.56, SD 11.93, p = 0.039) for those with < 4 hour symptoms than those with 4 hours of symptoms. CONCLUSION Symptom onset to balloon time has a greater impact on cardiac morbidity than door-to-balloon time.